Decolourization of anthraquinone reactive dye by electrochemical reduction on reticulated glassy carbon electrode - Carneiro, Patricia A. [UNESP] (2004)
The electrochemistry reduction for the removal of Reactive Blue 4 (RB4) dye from aqueous solution using reticulated glassy carbon electrode is investigated. At pH < 8.0 the anthraquinone group of the RB4 dye are reduced in one cathodic step to hidroquinone after a reversible two-electron process involving a precedent two protons reaction. A stable semiquinone is detected by spectrophotometric technique. At pH > 8.0 the reduction process involves two reversible 2-electron steps, whose species are generated by a protonation equilibrium of anthraquinone group. The results shows that 60% of color removal was obtained after 3 hours of RB4 dye electrolysis at acidic and neutral conditions and only 37% at alkaline conditions. Simultaneously 64% of total organic carbon was removed after electrolysis at pH 2.0.